Selenium Exposure and Incident Hypertension Among Chinese Adults (P24-020-19). (13th June 2019) - Liu, Liping; Lin, Gang; Wang, Huijun; Zhang, Bing; Du, Shufa
Abstract: Objectives: China is the epicenter of a major global increase in hypertension among low and middle-income countries. The burden of mortality, morbidity, and disability from hypertension in China has been shown to be the highest in absolute or relative terms globally. While some cross-sectional study reported higher selenium concentrations were associated with higher prevalence of hypertension, few longitudinal studies examined the association between selenium and incident hypertension. Methods: We used a sub-cohort data from a longitudinal study, the China Health and Nutrition Survey. We followed up 2530 non-hypertensive participants aged 20 – 65 years old who had selenium concentrations measured on toenail samples in 2009 through 2015. We defined hypertension as systolic pressure >140 mm Hg, diastolic pressure >90, diagnosed by physicians, or taking anti-hypertension medications. We measured selenium concentrations in toenail samples by using inductively coupled plasma mass spectrometry (ICP-MS), and used logistic regression models to estimate the association between selenium quartiles and incident hypertension. Results: The average selenium concentration was 0.41 (±0.23) mg/kg and the median was 0.39 mg/kg. The incidence of hypertension from the first to the fourth quartile was 28.3%, 25.2%, 25.0%, and 21.5%, respectively, with an average incidence of 24.4% during the six follow-up years. Compared to the fourth quartile (average selenium concentration 0.70 mg/kg and range 0.52 – 2.72), the relative risk (RR) was 1.46 (95% CI: 1.11 – 1.93), 1.29 (95% CI: 0.97 – 1.71), and 1.32 (95% CI: 1.00 – 1.75) from the first (lowest) to the third quartile, respectively, controlled for age, gender, body mass index, and some other cofounders. Conclusions: Low selenium concentrations increased the risk of hypertension among Chinese adults. More research is needed to fully understand the effects of selenium exposure on hypertension. Funding Sources: The Eunice Kennedy Shriver National Institute of Child Health and Human Development (NICHD), NIH; The Fogarty International Center, NIH; Chinese Center for Disease Control and Prevention.